2012
DOI: 10.2298/gensr1201101i
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of beech provenance regions in Serbia by spatial analysis of genetic diversity

Abstract: The results of spatial analysis of genetic diversity have practical application in the definition and delineation of regional provenances of forest trees. Research in this paper, was based on the material from 27 natural populations of beech in Serbia. The genetic component of the research is based on the analysis of RAPD markers from bulk samples, using 28 primers. The spatial component of the research is based on the geographical position of the studied populations. Grouping of the studied populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, differences between provenances can be detected in seed (Kuser & Ching 1981, Melzack & Watts 1982, Šijačić-Nikolić et al 2007, Rawat & Bakshi 2011, Caliskan 2014, seedlings (Stihl & Persson 1991, Varelides et al 2001, Ivetić et al 2005, Loha et al 2006, Ivetić & Škorić 2013, and patterns of spatial distribution can be observed as well (Ivetić et al 2012). Variation between populations may be clinal or ecotypic and knowledge on pattern of variation is important in cases of FRM transfer.…”
Section: Provenance (Population) Levelmentioning
confidence: 99%
“…However, differences between provenances can be detected in seed (Kuser & Ching 1981, Melzack & Watts 1982, Šijačić-Nikolić et al 2007, Rawat & Bakshi 2011, Caliskan 2014, seedlings (Stihl & Persson 1991, Varelides et al 2001, Ivetić et al 2005, Loha et al 2006, Ivetić & Škorić 2013, and patterns of spatial distribution can be observed as well (Ivetić et al 2012). Variation between populations may be clinal or ecotypic and knowledge on pattern of variation is important in cases of FRM transfer.…”
Section: Provenance (Population) Levelmentioning
confidence: 99%
“…In recent years, studies of forest genetic resources in Serbia were conducted on numerous tree species. Researches of molecular markers were focused mainly on investigation of genetic diversity in natural populations of European beech [38], Austrian pine and Scots pine [39][40][41][42], Serbian spruce [43], Sorbus spp. [44] and Sessile oak [45].…”
Section: Forest Genetic and Breeding Research In Serbiamentioning
confidence: 99%